Urinary ascitis in neonate with posterior urethral valve - Malvia, Sunny; Meena, Pradeep; Goyal, Suresh; Mehrotra, Juhi; Rawat, Ravi (International Journal of Contemporary Pediatrics, 2018)
Urinary ascites in a newborn infant is not very common. It indicates a disruption to the integrity of the urinary tract. Urinary tract obstruction leads to increased pressure which causes urine collection within the peri-renal spaces and subsequent urinary ascites either by calyceal perforation or filtration through the walls of urinary tract. Posterior urethral valve is most common cause of urinary tract obstruction in male child. The report describes a male child of age 17 days, presented with gross abdomen distension and diagnosed as urinary ascites, due to underlying posterior urethral valve. The abdominal distension was relieved with subsequent drainage of urine. Diagnosis was made using imaging techniques and corrective surgery planned.